Application Of The Problem-Based Learning Model To Improve Learning Outcomes Of Class X Biology Students At SMA Negeri 2 Tondano - Gabriel Gloria Lumentut; Orbanus Naharia; Ferny Tumbel (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the use of audio-visual media in Problem-Based Learning to improve student learning outcomes in tenth grade SMA Negeri 2 Tondano using classroom action research as the research methodology. (1) Planning, (2) Action, (3) Observation, and (4) Reflection are the four major phases of a cycle. In data analysis, the1percentage of completed student1learning outcomes is utilized. The research result was derived from student learning outcomes using two cycles; in cycle I, the1percentage of classical completion was 44.44 percent and in cycle II, it was 55.55 percent. It became a reference for the subsequent cycle's follow-up. The classical percentage of completeness for cycle II was then 92.59 percent complete and 7.40 percent incomplete. This demonstrated that it followed the research indicator in a conventional manner. Therefore, it is unnecessary to follow the subsequent cycle. This study concludes that using problem-based learning audio-visual as a learning medium for virus materials is crucial for improving student learning outcomes among students in1class X at SMA Negeri 21Tondano.